Transformational Leadership Strategies in Developing Life Skills Training Programs For Students of Paket C PKBM Suka Madju - Harianto, Agus; Riyanto, Yatim; Mardliyah, Sjafiatul; Yulianingsih, Wiwin; Zakariyah, M Fahmi (Universitas Negeri Padang, 2025)
This study aims to analyze the implementation of transformational leadership strategies in developing life skills training programs for Paket C students at PKBM Suka Madju. Using a qualitative case study approach, data were collected through in-depth interviews, observations, and document analysis to explore leadership dynamics and their impact on educational outcomes. The novelty of this study lies in examining transformational leadership within nonformal education, an area that has received limited attention compared to its application in formal education institutions. The findings indicate that transformational leadership significantly enhances program effectiveness by increasing student participation, aligning the curriculum with labor market needs, and integrating interactive, technology-based teaching methods. However, several challenges remain, including limited financial resources, low student motivation, and insufficient public awareness of the importance of nonformal education. To address these issues, PKBM Suka Madju continues to strengthen its institutional management, improve teacher development programs, and expand partnerships with industry and government agencies. The study highlights the need for sustained leadership development and collaboration to ensure the long-term success of life skills training programs in nonformal education. Keywords: Transformational leadership, life skills training, nonformal education, Paket C, PKBM Suka Madju.